2010
DOI: 10.1016/j.vetmic.2009.09.051
|View full text |Cite
|
Sign up to set email alerts
|

A socio-psychological investigation into limitations and incentives concerning reporting a clinically suspect situation aimed at improving early detection of classical swine fever outbreaks

Abstract: The aim of this study was to identify limitations and incentives in reporting clinically suspect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 18 publications
3
39
0
Order By: Relevance
“…A distrust in veterinary authorities and control measures is, indeed, listed as an important barrier to disease reporting (Bronner et al, 2014;Elbers et al, 2010;. Here again, the timeliness and reliability of compensation delivery intervene as critical elements in building trust between farmers and officials (World Bank, 2006).…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations
“…A distrust in veterinary authorities and control measures is, indeed, listed as an important barrier to disease reporting (Bronner et al, 2014;Elbers et al, 2010;. Here again, the timeliness and reliability of compensation delivery intervene as critical elements in building trust between farmers and officials (World Bank, 2006).…”
Section: Tablementioning
confidence: 99%
“…Cameron (2012) proposed that fear of the negative consequences of disease notification, poor relationship with veterinary services, and farmers' apathy toward disease occurrence and control are the main reasons for farmers failing to report (Cameron, http://dx.doi.org/10.1016/j.prevetmed.2017.01.002 0167-5877/© 2017 Elsevier B.V. All rights reserved. 2012).The results of a socio-psychological study among pig farmers in the Netherlands indicated that uncertainty about the occurrence of a given disease and the threat of a false alarm, which might have a negative impact on the farm and on the relationship between farmers and veterinarians, were important factors influencing farmer reporting (Elbers et al, 2010). Lack of trust in the control/eradication measures of veterinary authorities is also considered as a barrier to farmers' willingness to report (Elbers et al, 2010;.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These behaviors represent important targets for risk communication, since enhanced cooperation may reduce the size and severity of an outbreak. Some efforts have been made to understand producers' beliefs about disease reporting or on-farm disease control (Hopp et al, 2007;Heffernan et al, 2008;Palmer et al, 2009;Elbers et al, 2010;Delgado et al, 2012;Alarcon et al, 2014;Garforth et al, 2013) and the consequences of reporting on the severity of an outbreak Carpenter et al, 2011). However, other important producer behaviors which could impact the severity of a disease outbreak have received minimal attention.…”
Section: Introductionmentioning
confidence: 99%